From the Field to the Dashboard: Real-Time Readiness and Clinical Data Capture in U.S. Military Global Health Engagement Missions - Benjamin J Pass; Sabrina Torres; Jessica L A Jackson; Larissa F Weir; Chelsea B Payne; Emiko Rhodes; Luis M Jara; Aaron J Goodrich; Brian J Gavitt; Justin P Fox (Military Medicine, 2026)
Abstract Introduction Global Health Engagement (GHE) serves as a strategic tool for the Department of War to advance medical readiness and strengthen international partnerships. However, the Department lacks a standardized, real-time platform to document clinical workload and quantify readiness contributions. To address this gap, we developed and tested the Medical Currency Application for Readiness Tracking (MCART) 2.0 platform with U.S. Air Forces Southern (AFSOUTH). Materials and Methods From March 2024 to September 2025, we refined the legacy MCART 1.0 platform based on user feedback and tested the updated application across 12 AFSOUTH missions in the Caribbean, Central America, and South America. Built using secure Google Workspace tools, the modular platform captured data across four domains: clinical workload, Service-specific readiness metrics, biomedical equipment servicing, and site administration. MCART 2.0 integrated data entry, management, and visualization into a single workflow, enabling near-real-time access for mission leadership. Platform adoption was supported by AFSOUTH leadership and embedded Assessment, Monitoring, and Evaluation Champions. Primary outcomes included volume and type of clinical workload, number and category of readiness tasks, and qualitative themes from narrative entries. Structured data were analyzed descriptively while free-text responses were subjected to thematic analysis. This project was deemed exempt by the Uniformed Services University Institutional Review Board (DBS.2025.980) (ref #987775) on September 23, 2025. Results During implementation, 313 personnel submitted 16,466 records across 33 medical specialties spanning two Services. Service-specific readiness metrics accounted for 60.7% of entries, followed by procedural and diagnostic coding (32.5%) and site administration data. MCART 2.0 tracked 9,600 patient encounters and 4,600 clinical hours, captured 4,072 Current Procedural Terminology-coded procedures valued at 10,528 relative value units, and documented 143 biomedical equipment repairs. Narrative entries emphasized high-acuity cases, team-based training, operational challenges, and limited resources. User feedback guided iterative refinements to the interface, data fields, and visualization templates. Conclusions Field development and testing of MCART 2.0 demonstrated the implementation of a standardized, cross-service reporting tool for GHE activities, enhancing mission leadership’s ability to measure, communicate, and optimize the readiness and strategic value of these operations.